International Funds for Compensation for Human Rights Violations in International Law - Hassan, Shahd Hammad Mutar; Khalaf, Husam Abdul Ameer (Journal of Ecohumanism, 2025)
The establishment of international funds to compensate for human rights violations represents an important step towards achieving justice and equality between individuals and societies and solidarity among people, whether through providing financial assistance or by assuming legal and moral responsibility towards victims. With the development of international policies in recent decades, it has become necessary for states to assume their responsibilities in accordance with international law, not only in preventing and combating crimes, but also in providing means of redress for victims. Legislation in many countries has demonstrated the importance of fair compensation as part of criminal and social responsibility. Although traditional systems such as civil liability or direct insurance may be effective in some cases, the challenges facing victims of major crimes require specialized legal mechanisms to redress damage.